Prothrombin expression in cancer-derived cell lines - Dunjić Sofija; Cumbo Marija; Gvozdenov Maja; Tomić Branko; Pruner Iva; Radojković Dragica; Đorđević Valentina (Archives of Biological Sciences, 2019)
The link between thrombotic disorders and cancer has been known for over 150 years, although the precise mechanism of this relationship has not yet been resolved. Current data show that thrombin has a significant role in cancer metabolism, invasiveness, adhesion and survival. However, data regarding the expression of the thrombin precursor prothrombin in various cancer cell lines are scarce. Therefore, it was our objective to determine whether common cancer-derived cell lines (Caco-2, MCF-7, SK-BR-3, U-87 and U-251) express prothrombin. The prothrombin RNA expression level was assessed by qPCR, and the presence of prothrombin was analyzed by Western blot analysis. Our results show that Caco-2 cells originating from colorectal adenocarcinoma express prothrombin, whereas other analyzed cell lines do not. Our results provide a background for further research into the role of (pro)thrombin in cancer etiopathology. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. OI 173008]